TGFβ‐Responsive HMOX1 Expression Is Associated with Stemness and Invasion in Glioblastoma Multiforme. (4th July 2016) - Ghosh, Dhiman; Ulasov, Ilya V.; Chen, LiPing; Harkins, Lualhati E.; Wallenborg, Karolina; Hothi, Parvinder; Rostad, Steven; Hood, Leroy; Cobbs, Charles S.
Abstract: Glioblastoma multiforme (GBM) is the most common and lethal adult brain tumor. Resistance to standard radiation and chemotherapy is thought to involve survival of GBM cancer stem cells (CSCs). To date, no single marker for identifying GBM CSCs has been able to capture the diversity of CSC populations, justifying the needs for additional CSC markers for better characterization. Employing targeted mass spectrometry, here we present five cell‐surface markers HMOX1, SLC16A1, CADM1, SCAMP3, and CLCC1 which were found to be elevated in CSCs relative to healthy neural stem cells (NSCs). Transcriptomic analyses of REMBRANDT and TCGA compendiums also indicated elevated expression of these markers in GBM relative to controls and non‐GBM diseases. Two markers SLC16A1 and HMOX1 were found to be expressed among pseudopalisading cells that reside in the hypoxic region of GBM, substantiating the histopathological hallmarks of GBM. In a prospective study ( N = 8) we confirmed the surface expression of HMOX1 on freshly isolated primary GBM cells (P0). Employing functional assays that are known to evaluate stemness, we demonstrate that elevated HMOX1 expression is associated with stemness in GBM and can be modulated through TGFβ. si RNA‐mediated silencing of HMOX1 impaired GBM invasion—a phenomenon related to poor prognosis. In addition, surgical resection of GBM tumors caused declines (18% ± 5.1SEM) in the level of plasma HMOX1 as measured by ELISA, in 8/10 GBM patients. These findings indicate that HMOX1 is a robust predictor of GBM CSC stemness and pathogenesis. Further understanding of the role of HMOX1 in GBM may uncover novel therapeutic approaches. Stem Cells 2016;34:2276–2289 Abstract : Targeted proteomic analyses revealed elevated expressions of transmembrane proteinsHMOX1 and SLC16A1on the surface of glioblastoma cancer stem cells (CSCs) relative to healthy neural stem cells (NSCs). In the hypoxic region of the tumor, these proteins were found to be expressed among pseudopalisading glioma cells that also express known stem cell factors. From biological assays that are known to evaluate stemness, HMOX1 expression was found to be associated with stemness that could be regulated through TGFβ and PTEN signaling networks. Additionally, siRNA mediated inhibition of HMOX1 expression impaired cancer cell invasion. Together, this study demonstrates the association of HMOX1 expression with cancer stemness in glioblastoma and suggests a possible regulatory mechanism of CSC invasion and survival in the hypoxic region of the tumor.